Enzymatic Method for Continuous Monitoring of Inorganic Pyrophosphate Synthesis - Nyren, P.; Lundin, A.
A sensitive method for the analysis of inorganic pyrophosphate (PP,)which utilizes the enzymes ATP sulfurylase and firefly luciferase is described. The assay is based on continuous monitoring of the ATP formed in the ATP sulfurylase reaction using purified firefly luciferase. The assay can be completed in less than 2 s and is not affected by inorganic phosphate. The method has been used for continuous monitoring of formation Of PPi in Rhodospirillum rubrum chromatophores. The assay is extremely sensitive, the linear range of the assay being I . 10e9-5. IO-' M PPi. It is suitable for routine applications. It is also possible to use the method for determination of low amounts of adenosine S'phosphosulfate.
Keywords: LUMINESCENCE; INORGANIC ANALYSIS; PHOSPHATE COMPOUNDS; MEMBRANE-BOUND ENZYMES; PHOTOSYNTHESIS; BIOENERGETICS